Use of rapid diagnostic tests for diagnosis of malaria in the UK. Issue 8 (7th April 2006) - Chilton, D; Malik, A N J; Armstrong, M; Kettelhut, M; Parker-Williams, J; Chiodini, P L
Abstract : Background: Malaria is currently diagnosed almost exclusively by microscopy in clinical laboratories. The introduction of rapid diagnostic tests (RDTs) may be useful in achieving rapid detection of malaria parasites, especially in situations where malaria is not often seen or where staff are inexperienced. Aim: To explore the use of RDT in UK laboratories. Methods: The current use of RDTs was surveyed in UK laboratories subscribing to the United Kingdom National External Quality Assessment Scheme blood parasitology and haematology schemes. Results: An overall survey response rate of 60.3% was seen. RDTs were found to be the preferred choice, either alone or in conjunction with microscopy in 31.2% of the samples examined during normal working hours and in 44.3% of the specimens examined on call. Conclusions: During on-call hours, the use of RDTs was observed to increase and RDTs changed the diagnosis in 12% of laboratories. No established protocol for RDT use was, however, observed in the UK. A protocol that needs to be validated in the laboratory setting is suggested.